Can Legislative Reform Secure Rewards for Authors? Exploring Options for the New Zealand Copyright Act - Kenner, Lucy Elizabeth (Victoria University of Wellington Law Review, 2017)
Copyright law protects works, but not the authors who create them. As the weaker party in negotiations, authors face insufficiently remunerative bargains, often made early in their careers. The Copyright Act 1994 is currently under review, and reform should be considered. This article explores legislative mechanisms to secure rewards for authors from their works. It considers the contrasting schemes in the United States and in Germany and evaluates the desirability of adopting these approaches in New Zealand. The United States approach is a termination right that allows authors to recapture their copyrights after 35 years. The scheme in Germany requires that authors’ contracts meet minimum equitable standards or be subject to amendment. This article considers that there are significant problems with adopting either approach in New Zealand. These include the risk of harming authors overall, enforcement, the interests of disseminators, arbitrariness, uncertainty and administrative difficulties. This article recommends that neither option is desirable. It concludes that while there is a clear need for solutions, a cautious approach must be taken to any reforms which are intended to address such a complex problem.